Character Building in the Novel (The Hedgehogs on a Hot Day) - Assi, Azhar Ali (Thi Qar Arts Journal, 2024)
The character in the novel (The Hedgehogs on a Hot Day) by the author (Falah Rahim) played an important role; it was the beating heart of the novel as it created the events and gave vitality to time and place. The author utilized all techniques well and artistically in drawing the characters, striving to make them lively and lifelike, not cartoonish figures moved at the author’s whim. The main character is the narrator (Salim Kadhim), who narrates in the first person, tilting the novel towards an autobiographical approach. As for the secondary characters, some were supportive while others opposed and struggled against the main character. The author was able to clarify the dimensions of the character in the novel through external features, psychological descriptions, as well as their thoughts, beliefs, and social backgrounds. The author presented his characters in two ways: the first is reporting, which depends on drawing the character from the outside, such as appearance and clothing; the second is revelation through what others say about a character, as well as dialogue—both the external dialogue, which is the best means of introducing the character, and the internal dialogue, through which the character reveals all their feelings and emotions, and discloses their behavior and actions in response to events in reality.